EXPLORING THE CHILD-CENTRED MONTESSORI CURRICULUM - Zhou Yuan; Mohd Nazri Bin Abdul Rahman (P3I UMSurabaya, 2024)
The Montessori curriculum is one of the most popular types of kindergarten curriculum nowadays, which is also in accordance with the rules of physical and mental development of young children, and at the same time, the Montessori curriculum is also the favourite curriculum of many parents and teachers.In this paper, the authors used literature analysis and interviews with two kindergarten teachers in Montessori kindergarten in Taizhou City, Zhejiang Province, China, to explore the current status of Montessori curriculum implementation in kindergartens.